Analysis of Size, Return on Assets, Debt to Equity Ratio, and Total Asset Turnover Against the Value of Companies in Large Trade Sector Companies in Production and Consumer Goods Listed on the Indonesia Stock Exchange - Indah Rahayu Lestari; Riny Mustika (Sekolah Tinggi Manajemen IPMI, 2019)
This study aims to determine the Size, Return on Assets, Debt to Equity Ratio and Total Asset Turnover of FirmValue in Large Trade Sub-Sector Companies in Production and Consumption Goods 2013-2017. The sampling technique uses purposive sampling method. The population in this study were 37 companies and the samples used were 10 large trading companies producing and consuming goods listed on the Indonesia Stock Exchange. The method used in this study is the method of hypothesis testing (Hypothesis Testing). The data used are secondary data in the form of reports complete finance for the 2013-2017 period. The analytical tool used in this study is multiple linear regression analysis and tested using the Statistical Package for the Social Science (SPSS) Version 20.0 and Microsoft Excel 2010. The results of the research show that Return on Assets have a significant effect on Company Value, while size, Debt to Equity Ratio and Total Asset Turnover does not have a significant effecton Company Value.